Principle of geoengineering: Meteorological and geographical conditions of the Department of Junín for the generation of precipitation in agriculture - Mucha Huaire, Lilian Fiorella (2022)
Geoengineering attempts to remedy the climate crisis through the intervention of dynamic systems to mitigate future scenarios of water drought in agriculture. The provinces of the department of Junín were identified as having the meteorological and geographical conditions where precipitation should be generated for the benefit of agriculture. The meteorological data was obtained from SENAMHI for the period 2000-2020, cloud information derived from the GOES-16 satellite belonging to NOAA was used and the satellite images were resampled using the cubic convolution method to evaluate the cloud parameters under the bands (C05, C08, C10, C11, C13, C15 and C16) in areas with cloud altitude between 6-8 km in the Andes and in the eastern part between 5-7 km within the study area. From this analysis, favorable cloud clusters were identified in relation to the arid zones with extensive croplands where rainfed irrigation is used, using the geodatabase of the Ecological and Economic Zoning (ZEE) of the Regional Government of Junín.